PENAMBAHAN PENAMBAHAN PEKTIN, GULA, DAN ASAM SITRAT DALAM PEMBUATAN SELAI DAN MARMALADE BUAH-BUAHAN - Fesdila Putri Nurani (Journal of Food Technology and Agroindustry, 2020)
Quality degradation due to the process of respiration as well as physical, chemical and biological damage to the fruit is very undesirable because it caused indirectly shorten the shelf life of the fruit. Damaged fruit will have a low selling value. Various attempts were made to overcome these problems including of fruit chips, sweets, to fruit leather. In addition to these methods, fruit can also be processed into bread spread ingredients such as jam and marmalade. Jam is a thick or semi-solid food product made from crushed or chopped of fruit with added some sugar. Marmalade is a semi-solid food product made from fruit juice, sugar, citric acid, and includes pieces of fruit or fruit skin. Marmalade is generally made from citrus fruits, but nowadays marmalades are also made from other fruits. Both of jam and marmalade products involve the heating process and the use of high concentrations of sugar as a preservative. Several factors that influence the making of jam and marmalade include pectin, sugar, water and the presence of acids which are very influential in gel formation.